Treatment of the Mycobacterium chelonae Infection after Fat Injection - Kim, Seok-Kwun (Arch Plast Surg, 2015)
For recent years, use of autologous fat injection has increased significantly in facial contouring surgery. Along with such increase in use, complications like atypical mycoplasma infection have been also on the increasing trend. The authors report two cases of Mycobacterium chelonae infection that occurred after autologous fat injection. Patients were treated as infection that resistant to common antibiotics and results were negative to routine culture and Gram staining. Acid-fast bacillus stain, polymerase chain reaction (PCR) test and mycobacterial cultures were conducted for diagnosis under suspicion of atypical mycoplasma infection. Then, combination antibiotics therapy, surgical treatment, and steroid injection were performed for treatment. Both patients were diagnosed with Mycobacterium chelonae in PCR test. They were positive to mycobacterial cultures. Combination antibiotics therapy was repeated to improvement of symptom. However, they could not be free from side effects such as deformation in facial contour, scar and pigmentation even after full recovery. When chronic wound infections after autologous fat injection, we must suspect atypical or mycobacterial infection and conduct examinations for a early diagnosis and proper antibiotic therapy that is effective to the nontuberculous mycobacteria.